Peningkatakan Motivasi Belajar Peserta Didik Kelas III melalui Metode Role Play Di SDN Model Mataram Tahun 2024 - Anggraini, Ismi; Nisa, Khairun; Supriatin, Dwi (Mataram University, 2025)
In the learning process, teachers should not only focus on students’ learning outcomes but also pay attention to the learning process itself and the factors that support the effectiveness of learning, one of which is learning motivation. This study aims to improve students’ learning motivation through the Role Play method at SDN Model Mataram. The research employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection stages, while also examining the implementation of learning activities using the Role Play method. Data were collected through observation of learning implementation and questionnaires. Data analysis was carried out using quantitative techniques based on questionnaire results. The findings indicate an increase in students’ learning motivation from 76.81% in the first cycle to 86.61% in the second cycle. Therefore, it can be concluded that the Role Play method effectively enhances students’ learning motivation.